Antibacterial Activities Test of the Curcuminoid Compound in the Endophytic Bacteria of Curcuma zanthorrhiza Roxb. - Utami, Ulfah; Fuadati, Choirul; Perdana*, Terry Angria Putri (Proceedings of the International Conference on Green Technology, 2017)
This study aims to determine the active compound curcuminoid contained in secondary metabolites 2 endophytic bacteria of temulawak ( Curcuma zanthorrhiza Roxb.) rhizome BT2 and PD2 potentially as antibacterial compounds. TLC method used for separation of curcuminoid compounds followed by contact bioautography test to know the ability of compound activity which has been separated through TLC in inhibiting the growth of bacteria. The results of curcuminoid compound separation by TLC method are curcumin can be detected in BT2 and PD2 endophytic bacteria in the 4 th spot with the same values of Rf 0.43. The desmetoxicurcumin fraction can be detected in BT2 and PD2 in the 3 rd spot with the values of Rf 0.39 and 0.38 respectively. While bisdesmetoksikurkumin fraction can be detected in BT2 and PD2 in the 1 st and 2 nd spot with the value of Rf 0.25 and 0.32 respectively. Testing of contact bioautography on TLC plate containing separation of curcuminoid compounds produced by BT2 and PD2 doesn’t show any antibacterial activity.